Expression of interfacial Seebeck coefficient through grain boundary engineering with multi-layer graphene nanoplatelets. Issue 11 (1st October 2020) - Lin, Yue; Wood, Maxwell; Imasato, Kazuki; Kuo, Jimmy Jiahong; Lam, David; Mortazavi, Anna N.; Slade, Tyler J.; Hodge, Stephen A.; Xi, Kai; Kanatzidis, Mercouri G.; Clarke, David R.; Hersam, Mark C.; et al.
Abstract : Expression of energy filtering to boost thermoelectric performance through grain boundary engineering utilising graphene. Abstract : Energy filtering has been a long-sought strategy to enhance a thermoelectric material's figure of merit zT through improving its power factor. Here we show a composite of multi-layer graphene nanoplatelets (GNP) and n-type Mg3 Sb2 leads to the expression of an energy filtering like effect demonstrated by an increase in the material's Seebeck coefficient and maximum power factor, without impact on the material's carrier concentration. We analyse these findings from the perspective of a heterogeneous material consisting of grain and grain boundary phases, instead of a more traditional and common analysis that assumes a homogeneously transporting medium. An important implication of this treatment is that it leads to the development of an interfacial Seebeck coefficient term, which can explain the observed increase in the material's Seebeck coefficient. The contribution of this interfacial Seebeck coefficient to the overall Seebeck coefficient is determined by the relative temperature drop across the grain boundary region compared to that of the bulk material. In Te doped Mg3 Sb2 we show the introduction of GNP increases the interfacial thermal resistance of grain boundaries, enhancing the contribution of the interfacial Seebeck coefficient arising from grain boundaries to the overall Seebeck coefficient. Without significant detriment to the electrical conductivity this effect results in a net increase in maximum power factor. This increased interfacial thermal resistance also leads to the synergistic reduction of the total thermal conductivity. As a result, we enhance zT of the Mg3 Sb2 to a peak value of 1.7 near 750 K. Considering the two-dimensional nature of the grain boundary interface, this grain boundary engineering strategy could be applied to a few thermoelectric systems utilizing various two-dimensional nanomaterials.